The ethics of theft: Reevaluating the impacts of floral larceny on plant reproductive success - Jin-Ru Zhong; Xiao-Fang Jin; Michael C. Orr; Xiao-Qing Li; Yong-Deng He; Sheng-Wei Wang; Qing-Feng Wang; Chun-Feng Yang; Zhong-Ming Ye (Plant Diversity)
Plants and their interaction partners offer unparalleled views of evolutionary ecology. Nectar larceny, entailing nectar extraction without pollinating, is thought to be an example of a harmful, antagonistic behavior, but the precise consequences of floral larceny on plant reproductive success remain contentious. We conducted a comprehensive meta-analysis of 153 studies across 120 plant species, using 14 moderators to assess the effects of floral larceny on plant reproductive success and examine the key moderators. We found that floral larceny negatively impacts flower traits, pollinator visitation, pollen deposition, and fruit set, while having a neutral effect on critical female fitness indicators, such as seed set and seed quality, as well as on male fitness. By altering pollinator behavior, floral larceny may reduce geitonogamy, potentially enhancing genetic diversity. Additionally, factors such as pollinator type, plant mating system, and pollen limitation were identified as key moderators of these effects. Our analysis reveals an ultimately neutral effect of floral larceny on plant reproductive success, with potential benefits in certain contexts. These findings suggest that floral larceny plays a complex and multifaceted role within plant-pollinator interactions, facilitating the evolutionary stability and coexistence of floral larcenists and host plants.